Prompt blood transfusion is the only treatment option for correction of moderate to severe anemia in diabetic foot/leg ulcers: experience from a tertiary health facility in southeastern Nigeria - Nkpozi, Marcellinus O; Bozimo, Gesiye E; Nzechukwu, Goodness I; Okeke, I Maureen; Ubani, Blessing C; Onwuchekwa, Uwa N (Journal of Drug Delivery and Therapeutics, 2025)
Background/introduction: Anaemia is a common complication in patients with diabetic foot/leg ulcers (DFU) and the severity of the anaemia is a predictor of non-healing ulcers, amputation and mortality. Identification and prompt treatment of cormorbid conditions such as anaemia play a critical role in the healing of DFUs. The objective of this study was to show that the identification and prompt correction of anaemia improved outcome in patients with DFU Methods and methodology: This was a prospective study of a case series of 10 patients admitted and managed for various degrees of DFU with or without gangrene in the medical wards of Abia State University Teaching Hospital (ABSUTH), Aba, southeast Nigeria from June 1, 2024 to September 30, 2024. Results: Ten patients (5 males and 5 females) were enrolled in this case series with a mean age of 56 ± 9.88 years and an age range of 35 to 68 years. Five of the patients who were not anaemic at admission and during hospitalization needed no blood transfusion for their wounds to heal completely while all the four patients who had moderate to severe anaemia at presentation and had foot ulcers with gangrene of their one or more digits (Keith Wagner grade 4) and required limited amputations received several units of blood transfusion. The fifth patient who was anaemic at presentation but no gangrene (Keith Wagner grade 2) received only one unit of blood. Conclusion/Recommendation: This study has shown that moderate to severe anaemia at presentation or while hospitalization of diabetic foot ulcer with gangrene of the digit(s) required prompt blood transfusions before healing of the wound could occur. It is, therefore, recommended that diabetic patients with foot ulcers must continually be assessed for any form of anaemiaand promptly transfused if moderate to severe anaemia is present. Keywords: Anaemia, blood transfusion, diabetic foot/leg ulcer, Nigeria, treatment option.